Immunomodulatory activities of isolated compounds from the root-bark of Cussonia arborea. (1st January 2017) - Oladimeji, Abdulkabir Oladele; Oladosu, Ibrahim Adebayo; Jabeen, Almas; Faheem, Aisha; Mesaik, Mohammed Ahmed; Ali, Muhammad Shaiq
Abstract: Context: Cussonia arborea Hochst. ex A. Rich (Araliaceae) is a folk medicine used to treat various diseases. However, there is no report of the root phytochemistry. Objective: This study isolates and identifies the immunomodulatory compounds from root-bark of C. arborea . Materials and methods: The methanol extract (18 g) was subjected to repeated column chromatography resulting in isolation of five compounds (1 –5 ). Structure determination was achieved by analysis of their 1 D and 2 D NMR, and mass spectroscopy. The compounds (100–1.0 μg/mL) were examined immunomodulatory for effect on production of reactive oxygen species (ROS) from whole blood phagocytes and on proliferation of T-cells. The compounds cytotoxicity (100–1.0 μg/mL) was evaluated on NIH-3T3 normal fibroblast cells. Results: Three pentacyclic triterpenoids [3, 23-dihydroxy-12-oleanen-28-oic acid (1 ), 3β-hydroxylolean-12-en-28-oic (2 ) and 23-hydoxy-oxo-urs-12-en-28-oic acid (5 )], two phytosterols: [stigmasterol (3 )] and [3- O -β-d -glucopyranosyl stigmasterol (4 )] were all isolated from the methanol soluble extract. All the tested compounds (1 –4 ) were found to be nontoxic on NIH-3T3 cells. Compound 1 and 2 moderately inhibited the production of ROS (IC50  = 24.4 ± 4.3 and 37.5 ± 0.1 μg/mL, respectively) whereas compound 2 exhibited the highest inhibitory effect (IC50  = 12.6 ± 0.4 μg/mL) on proliferation of phytoheamagglutinin (PHA) activated T-cells. Conclusions: The isolated compounds (1 –5 ) are reported for the first time from this species. In addition, compound 2 with suppressive potential on production of intracellular ROS and proliferation of T-cells could be of immense value in control of autoimmune diseases as well as in immune compromised patients.